2022
DOI: 10.1111/maec.12695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ecology of a shallow water shrimp, Acetes sibogae sibogae Hansen 1919: Evidence for strongly limited gene flow across the western Pacific

Abstract: The shallow water shrimp Acetes sibogae sibogae is an ecological and economically important organism in the Asian region. We assessed the genetic diversity and population structure of this species based on samples obtained from eight sites in Japan, the Philippines and Indonesia. Nucleotide sequence analyses were performed based on PCR‐amplified mitochondrial DNA fragments comprising the control region and part of the 12S rRNA gene. In total, 656 bp nucleotide sequences were obtained from 377 individuals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 103 publications
2
9
0
Order By: Relevance
“…The Wallace Line, which divides Indonesia into two physically distinct parts, has been demonstrated to have a significant influence on genetic variations in numerous marine species between the east and west region [3]. [4] [5]. Similar findings were found in a prior investigation that used sequencing data from four molecular markers (two mitochondrial and two nuclear) [26].…”
Section: Discussionsupporting
confidence: 79%
“…The Wallace Line, which divides Indonesia into two physically distinct parts, has been demonstrated to have a significant influence on genetic variations in numerous marine species between the east and west region [3]. [4] [5]. Similar findings were found in a prior investigation that used sequencing data from four molecular markers (two mitochondrial and two nuclear) [26].…”
Section: Discussionsupporting
confidence: 79%
“…Whether this also affects marine animals is still a mystery. recent studies on marine taxa across the target location of this study have reported population structures such as crustaceans (Hardianto, Fukuchi, et al., 2022; Hardianto, Wijayanti, et al., 2022; Wainwright et al., 2020a), fish (Ackiss et al., 2013; Hardianto et al., 2023), coral reef (Wainwright et al., 2020b), sea urchin (Wainwright et al., 2019) and shellfish (Kusnadi et al., 2022). The structured populations were attributed to several factors including historical and contemporary interplay among a complex set of ecological, demographic, behavioural, genetic, oceanographic, climatic and/or tectonic processes.…”
Section: Introductionmentioning
confidence: 76%
“…Whether this also affects marine animals is still a mystery. recent studies on marine taxa across the target location of this study have reported population structures such as crustaceans (Hardianto, Fukuchi, et al, 2022;Wainwright et al, 2020a), fish (Ackiss et al, 2013;, coral reef (Wainwright et al, 2020b), sea urchin (Wainwright et al, 2019) and shellfish (Kusnadi et al, 2022).…”
mentioning
confidence: 75%
See 2 more Smart Citations